The communication in simulated learning environments - Vaca Barahona, Byron (2016)
The aim of this research is to describe how the virtual learning environments that integrate 3D simulations encourage communication, interaction and collaboration of students. This research uses a qualitative methodology based on the systematic observation. The results show that students - based on experience in 3D simulation environments - become active agents in the construction of their learning process. The 3D simulationenvironments with pedagogical mediation encourage communication and interaction of students in the context of the teaching sequence promoting the learning of students, and generating two types of communication: interaction between participant and object 3D; and interaction between participants that develops spontaneously and in larger quantities.